A combination method of the theory and experiment in determination of cutting force coefficients in ball-end mill processes. Issue 4 (23rd June 2015) - Kao, Yung-Chou; Nguyen, Nhu-Tung; Chen, Mau-Sheng; Huang, Shyh-Chour
Abstract: In this paper, the cutting force calculation of ball-end mill processing was modeled mathematically. All derivations of cutting forces were directly based on the tangential, radial, and axial cutting force components. In the developed mathematical model of cutting forces, the relationship of average cutting force and the feed per flute was characterized as a linear function. The cutting force coefficient model was formulated by a function of average cutting force and other parameters such as cutter geometry, cutting conditions, and so on. An experimental method was proposed based on the stable milling condition to estimate the cutting force coefficients for ball-end mill. This method could be applied for each pair of tool and workpiece. The developed cutting force model has been successfully verified experimentally with very promising results.